Pengaruh Metode Eksperimen terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Agustinus Tanggu Daga; Imakulata Magi Loda; Apliana Dapa Loka (Paedagogie, 2026)
This study aims to examine the impact of the experimental method on science learning outcomes for 28 third-grade students at Weerame Christian Elementary School, divided equally into experimental (n=14) and control (n=14) groups. The experimental group used direct instruction. Data came from a validated 20-item multiple-choice test. Descriptive analysis revealed notable gains: the experimental group's mean pretest score was 50.68 (range: 35-60), rising to 85.23 posttest (range: 60-95; N-Gain=0.70, high effect). The control group's mean improved from 49.09 (33-75) to 61.45 (40-80; N-Gain=0.24, low effect). Pretest equality was confirmed (mean difference=1.59; p>0.05). Prerequisite tests showed normality (sig.=0.161) but marginal homogeneity (sig.=0.017). Independent Samples t-test yielded sig.=0.000 <0.05, indicating a significant posttest difference favoring the experimental group. It is therefore concluded that the experimental method influences science learning outcomes in third grade at SDM Weerame. Teachers should integrate it into science lessons under Merdeka Curriculum on elementary shcool.